Development and Implementation of an Innovative Virtual Laboratory for Acid-Base Titrations to Improve Chemistry Learning Outcomes - Lara, Setia; Situmorang, Manihar (Universitas Lampung, 2024)
The use of virtual laboratories needs to be encouraged to adapt students' daily digital lives. This study aims to provide a virtual laboratory as multimedia for teaching Acid-Base Titration. The research was conducted involving class XI Science students, grouped into experimental class and control class. The research include providing an innovative virtual laboratory for the topic of Acid-Base Titration, and implementing it for chemistry teaching. The virtual laboratory has been packaged on a Web basis for hybrid learning, implemented in experimental classes, through short teaching, explanations on how to use virtual, and giving assignments. The control class was given conventional teaching with assignments. The research results showed virtual laboratories are effective in facilitating students' active learning. Sequential student learning outcomes from assignment results in the experimental class (M=84.80±6.90) were higher than the control class (M=78.24±7.45), posttest scores in the experimental class (M=83.00±4.95) were also higher than control class (M=65.40±7.02), and the two were significantly different (t-test 10.244 > t-Crit. 1.677). Learning chemistry using a virtual laboratory gives the impression of long-remembered learning, and is a good strategy for improving learning outcomes. Virtual laboratories are very interesting and are a new approach to motivate students to learn optimally.Keywords: Virtual Laboratory, Acid-base titration, Learning outcomes, Active learning, Chemistry TeachingDOI: 10.23960/jppk.v13i3.30630